PERAN KOMITMEN ORGANISASI DALAM MEMEDIASI PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KUALITAS SUMBER DAYA MANUSIA, DAN SARANA PRASARANA TERHADAP KINERJA ASN PADA SEKTOR PUBLIK - Abdul Jalil; Eni Rahmawati; Nizmayavira (Program Studi Manajemen Keuangan Syariah IAIN Parepare, 2026)
This study investigates the mediating role of organizational commitment in linking transformational leadership, human resource quality, and infrastructure support to employee performance within the public sector. Drawing on organizational behavior and human resource management perspectives, this research addresses the ongoing debate regarding the relative importance of leadership, structural support, and employee capability in shaping performance outcomes in bureaucratic institutions. A quantitative survey was conducted among civil servants at the Regional Office of the Ministry of Religious Affairs in Central Sulawesi Province. Using purposive sampling, data were collected from 64 respondents out of a population of 175 employees. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that transformational leadership does not exert a significant direct effect on either employee performance or organizational commitment. Human resource quality demonstrates a positive and significant effect on performance, while its influence on organizational commitment is not statistically significant. Infrastructure support significantly enhances organizational commitment but does not directly influence performance. Moreover, organizational commitment neither significantly affects employee performance nor mediates the relationships among the exogenous variables and performance. These results highlight that, in a bureaucratic public sector context, performance is primarily driven by employee capability rather than leadership style, infrastructural support, or affective attachment. The study contributes to the literature by challenging the assumed centrality of leadership and commitment in public sector performance and underscores the need to prioritize competency development and performance-oriented systems.